THE BEST IN LOBBY DESIGN HOTELS & OFFICES - Phillips, Alan, author 342679; Croot, Viv, editor 590344 (Mies, Switzerland : ROTOVISION, 1991)
THE BEST IN LOBBY DESIGN : HOTELS AND OFFICES offers a scrupulously edited contemporary review of the best work in this area, citing examples from architects worldwide. An introductory essay explains the philosophy and function of the lobby; subsequent chapters are devoted to essays on four major expressions of style that preoccupy contemporary architecture and design: Modern, Interventionist, Traditional and New Modern. Within each chapter, the style is defined in the abstract and its application to lobby design in particular is explored. THE BEST IN LOBBY DESIGN: HOTELS AND OFFICES offers an outstanding guide to any such exploration, being at once a catalogue of excellence and a comprehensive source book that celebrates, informs and inspires.